Bounded Blame: The Effects of Victim–Perpetrator Relationship and Victimization History on Judgments of Sexual Violence. Issue 15 (August 2021) - Catlin, Mary; Scherr, Kyle C.; Barlett, Christopher P.; Jacobs, Erin; Normile, Christopher J.
Individuals often tend to irrationally blame victims for their plight. This research incorporated a bounded rationality framework to examine first-person perspectives (rather than third-person) of both victims' and nonvictims' perceptions and judgments of acquaintance and stranger sexual violence. Upon completing individual difference measures, including a just-world belief assessment, participants ( N = 296) were randomly assigned to read a scenario in which the vignette victim was either acquainted with or had no prior relationship with the perpetrator. Then, taking the perspective of the vignette victim, participants offered four judgments: the likelihood of reporting the crime, self-blame, perceived control, and sympathy expected from others. Results showed that instances of acquaintance sexual violence were judged more negatively than instances of stranger sexual violence. Moreover, participants who had previously experienced sexual violence reported more negative judgments than nonvictims (except for sympathy expected from others). An exploratory path analysis indicated that as nonvictims', but not victims', just-world beliefs became stronger, they indicated a higher willingness to report the crime, perceived more control over the situation, and expected more sympathy from others. We end with a discussion of how the present research can advance our understanding of sexual violence by using a bounded rationality framework and discuss the practical implications that the observed effects have for professionals in the legal system, outside observers, and victims themselves.